Engineering Pedagogy as the Basis for Effective Teaching Competencies of Engineering Faculty - T. Rüütmann (Moscow Polytechnic University, 2019)
The article presents the philosophy and the basics of Engineering Pedagogy Science - the key to science-based, effective, interactive and motivating teaching engineering, shaping the ground of teaching competencies of engineering faculty, ensuring relevantly one of the prerequisites of the quality of engineering education in general. The foundational questions shaping the philosophy of Engineering Pedagogy Science, as an analytical ground for effective course design and further course development, based on informed decisions, are presented in this paper. The didactic pentagram and the basic didactical model of Engineering Pedagogy Science are discussed in this paper. Didactical pentagram of Engineering Pedagogy Science forms the ground of the essential pedagogical competencies of engineering faculty along with the speciality competencies, ensuring effective teaching engineering. The basic didactic model of Engineering Pedagogy Science follows the principles of an iterative process, being an effective tool for the design of a study program, curriculum, syllabus, course, or a lecture with the aim of effective teaching engineering. Integrated quadruple instructional model of Engineering Pedagogy Science as the foundation of integrated course design and one of the preconditions of effective teaching and learning is introduced as the basis of expected teaching competencies of engineering faculty. Pedagogical competences of the faculty are becoming more considerable in the quality assessment of higher education. The most effective ground of pedagogical continuing education of engineering faculty is Engineering Pedagogy Science, which offers suitable and relevant didactic models for insurance of effective teaching and learning and integrated course design based on informed decisions, learning analytics, reflection and metacognition.